Traditional and Christian elements in contemporary pictorial African art in South Africa with special reference to the works of John Muafangejo, Azariah Mbatha and Dan Rakgoathe - Kilian, Julie (Rhodes University, Faculty of Humanities, Department of Fine Art, 1987)
Art is the outward, visual manifestation of the undying soul of a people. The genius displayed in the day to day articles produced in traditional tribal society is equally present in the art produced by the Contemporary African Artist. The Contemporary African Artist finds himself in an interesting position, in that he is, at one time, a part of two different worlds, two different cultures, has taken place, the and his art provides evidence of the acculturation that coming together of indigenous, traditional African culture and 'European' or 'Western' culture. It follows that the contemporary African artist's work would display characteristics and elements derived from both of these worlds, since art is not created in a vacuum, but is, invariably, the outward, visible expression and symbol of an artist's environment, culture, emotional and intellectual responses and his beliefs. The study of Contemporary African Art reveals that despite the many divergences from the traditional or classic forms, a great many traditional influences and characteristics still persist in the same. An analysis of Contemporary African Art will also show that a significant body of works bear a marked influence of Christian teachings and biblical themes, as well as the influence of exposure to various forms of Swedish Medieval, Byzantine, Romanesque and Carolingian art.
Keywords: Muafangejo, John N., 1943-1987 -- Criticism and interpretation; Christian art and symbolism -- South Africa; Mbatha, Azariah -- Criticism and interpretation; Rakgoathe, Dan -- Criticism and interpretation; Art, Black -- South Africa